Application of Duplication Strategy In 4g For Better Accessibility To Network (International Journal of Scientific Research and Management (IJSRM), 2013)
During the last few decades, mobile communication has developed rapidly. The increasing dependency of people on telecommunication resources is pushing even more current technological developments in the mobile world. In Real-time multimedia applications, such as Live TV or live movie, video conferencing, VoIP, on-line gaming etc. are exciting applications to the success of 4G. In today’s Internet these applications are not subject to blocking, therefore the growth of popularity of these applications may endanger the stability of the Internet. In this paper, we propose a novel model to havemore accessibility to network through duplication strategy.